Modeling methodology for defining a priori the hydrodynamics of a dynamic suspension bioreactor. Application to human induced pluripotent stem cell culture. (20th September 2019) - Isu, Giuseppe; Morbiducci, Umberto; De Nisco, Giuseppe; Kropp, Christina; Marsano, Anna; Deriu, Marco A.; Zweigerdt, Robert; Audenino, Alberto; Massai, Diana
Abstract: Three-dimensional dynamic suspension is becoming an effective cell culture method for a wide range of bioprocesses, with an increasing number of bioreactors proposed for this purpose. The complex hydrodynamics establishing within these devices affects bioprocess outcomes and efficiency, and usually expensive in vitro trial-and-error experiments are needed to properly set the working parameters. Here we propose a methodology to define a priori the hydrodynamic working parameters of a dynamic suspension bioreactor, selected as a test case because of the complex hydrodynamics characterizing its operating condition. A combination of computational and analytical approaches was applied to generate operational guideline graphs for defining a priori specific working parameters. In detail, 43 simulations were performed under pulsed flow regime to characterize advective transport within the device depending on different operative conditions, i.e., culture medium flow rate and its duty cycle, cultured particle diameter, and initial particle suspension volume. The operational guideline graphs were then used to set specific hydrodynamic working parameters for an in vitro proof-of-principle test, where human induced pluripotent stem cell (hiPSC) aggregates were cultured for 24 h within the bioreactor. The in vitro findings showed that, under the selected pulsed flow regime, sedimentation was avoided, hiPSC aggregate circularity and viability were preserved, and culture heterogeneity was reduced, thus confirming the appropriateness of the a priori method. This methodology has the potential to be adaptable to other dynamic suspension devices to support experimental studies by providing in silico -based a priori knowledge, useful to limit costs and to optimize culture bioprocesses.